VALUABLE SPICE-AROMATIC VEGETABLE – MONARDA CITRIODORA L. - L. V. Bespalko; E. V. Pinchuk; I. T. Ushakova (Овощи России, 2018)
One of valuable spice-aromatic vegetable of Lamiaceae family is lemony monarda (Monarda citriodora L.) cultivated as nonperennial crop in most of regions of Russian Federation. Information regarding its parentage and biological special aspects are described here in this article. Brief review regarding nutritional quality and pharmaceutical importance as well as description of four cultivars of lemony monarda (which are currently included to Russian State register of selection invention and approved for usage, two of these cultivars Mona Lisa and Simka were selected and cultivated by Federal Scientific Vegetable Center are given here in this article. Main directions for up-to-date selection and application and practical usage of lemony monarda were indicated. In the field of creation of up-to-date vegetable cultivars, one of the main directions is selection of such a cultivars with high content of biologically active compounds for improvement of antioxidative activity and applicability for its cultivation at hydroponic plant with frame area to provide fresh green vegetables for people all year round. Simka cultivar meets requirements mentioned above and can be cultivated at various types of hydroponic plants including horizontal (salad lines, seedling tables) and vertical (multilayer hydroponics) types using natural (drag turf) or artificial (mineral wool blocks) substrates. This article also describes the main elements of technology of cultivation of lemony monarda in the open and protected ground to get green products and seed production. The features of the preparation of raw materials with a high content of biologically active compounds for fresh consumption and as a spicy-aromatic dry seasoning for salads, meat dishes, as a natural preservative and aromatic of jam, tea and other drinks are shown.